Edukasi Dampak Pernikahan Dini Terhadap Kesehatan Reproduksi Remaja Di Kelurahan Mafututu Kepulauan Tidore - Hardianti, Richa Novyana; Bansu, Istiana Asrari (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Early marriage in Indonesia is an important issue that affects adolescent reproductive health. Based on law number 16 of 2019 concerning Amendment to Law Number 1 of 1974 concerning Marriage, the minimum age limit for marriage is 19 years, but many teenagers in Indonesia marry at an age below that. Early mattiage can cause varios bad impact, especially for teenagers physical and mental health, such as the risk of pregnancy complications, premature birth and psychological disorders. Therefore, education about the dangers of early marriage is very important to increase awareness among teenagers. This community service activity at MAS Nurulhudah, Mafututu Village, Tidore Islands aims to increase teenagers' knowledge about the impact of early marriage on reproductive health. A total of 70 students took part in activities carried out using a peer group approach. This method allows students to discuss openly and share information about early marriage and its impacts. Before the activity, a pre-test was carried out which showed that 20 students had good knowledge, 30 students had moderate knowledge, and 20 students had poor knowledge. After the activity, the post-test results showed a significant increase in participants' knowledge. The number of students with good knowledge increased to 45 people, while students with moderate knowledge decreased to 15 people, and students with poor knowledge decreased to 10 people. This increase indicates the effectiveness of the peer group method in increasing teenagers' understanding of the dangers of early marriage on reproductive health. It is hoped that this activity will have a positive impact in reducing the rate of early marriage among teenagers and increasing their awareness of the importance of delaying marriage until a more mature age. Education through peers has proven to be effective in providing information that is more easily accepted by teenagers, as well as encouraging them to be more concerned about reproductive health issues.